Alterations in cathepsin H activity and protein patterns in human colorectal carcinomas - Re, E C del (Nature Publishing Group, 2000)
Our analyses of cathepsin H activity levels and protein forms in human colorectal cancers compared to matched control mucosa support the concept that altered proteinase expression patterns may reflect both cancer stage and site. Cathepsin H-specific activity was significantly increased in colorectal cancers compared to control mucosa (P = 0.003;n = 77). Highest specific activities and cancer/normal ratios (C/N) for activity were measured in Dukes' B and C stage carcinomas, cancers involved in local spread and invasion to lymph nodes. In contrast, cathepsin B and L activities analysed in the same paired extracts had been shown to be most frequently elevated in earlier stage carcinomas (Dukes' A and B), confirming that cathepsin H demonstrates a distinct pattern of expression during colorectal cancer progression. Although cathepsin H activities were most commonly elevated in Dukes' C cancers at all colon sites, both specific activity and C/N ratios were significantly higher for cancers of the left colon compared to other colon locations. A subset of 43 paired extracts analysed on Western blots also revealed consistent changes in cathepsin H protein forms in cancers. Normal mucosa typically showed a strong protein doublet at 31 and 29 kDa while cancers demonstrated decreased expression or total loss of the 31 kDa protein (90% of cases), equal or increased expression of the 29-kDa protein (67% of cases) and the new appearance or up-regulation of a cathepsin H band at 22 kDa (78% of cases). C/N ratios for cathepsin H enzyme activity correlated significantly with C/N ratios for the 29 kDa mature single-chain protein form (P< 0.001), with increased activity most commonly associated with elevated expression of 29-kDa cathepsin H but also with up-regulation of the 22-kDa band, suggesting a shift to more fully processed, mature active cathepsin H protein forms in cancers. Changes in cathepsin H expression were also detected by immunohistochemistry as elevated cathepsin H staining in tumour epithelial cells. © 2000 Cancer Research Campaign